Cytotoxicity of Trichoderma Reesei Extract in Hepa1-6 Cancer Cells - Seyyed Mehdi Sajadi; Farzad Katiraee; Amir Ali Shahbazfar; Hossein Tayefi Nasrabadi; Aliasghar Fakhri Demeshghieh (Fasa University of Medical Sciences, 2022)
Background & Objective: In the last decades, many successful anticancer fungal metabolites have been obtained, and fungi have shown great potential to produce beneficial anticancer drug compounds. In this article, the effects of the reference strain of Trichoderma reesei ethanolic extract on the Hepa1-6 cell line were studied. Materials & Methods: The fungus was initially cultured in the potato dextrose agar media, and then, it was transferred to yeast peptone dextrose broth. Afterward, the ethanolic and aquatic extracts were prepared, and were analyzed by chromatography and mass spectrometry (GC-MS). Then, the cell lines were treated with different doses of the extracts. The cytotoxic activity of fungal extracts were evaluated by MTT assay, Ferric reducing ability of plasma (FRAP) assay and Ferric Reducing Antioxidant Power (FRAP) Assay. Alkaline phosphatase (ALP) and Lactate dehydrogenase (LDH) measurement tests were done on the culture and cell fractions. Hematoxylin & Eosin staining was performed for microscopic studies, and an oxidant attack-antioxidant defense test was performed on the cell fraction. Results: GC-MS determined compounds such as cineal, cyclohexene, hydroxyethyl benzaldehyde, terpinenyl acetate, dihydro esthophyllene, propionic acid, hexadecanoic acid, and octadecanoic acid were extracted from the fungal extract. The half maximal inhibitory concentration (IC50) was between 7-8%, and the highest cytotoxic effectiveness was 10-15%. An increase in the levels of ALP, LDH enzymes, and total protein was observed. Conclusion: Therefore, the findings suggest that the extract of T. reesei has inhibitory effects on Hepa1-6 cancer cell lines.